Computational biomechanical analysis of medial displacement calcaneal osteotomy placement and orientation - Cecily James Marden; Bo Aletha Pilarczyk; Aaron Bhattachan; Willem Koenders; Bedri Karaismailoglu; Soheil Ashkani-Esfahani; Omer Subasi (Proceedings of the Institution of Mechanical Engineers, Part H: Journal of Engineering in Medicine, 2026)
Medial displacement calcaneal osteotomy (MDCO) is commonly used to correct valgus hindfoot alignment in progressive collapsing foot deformity, but the biomechanical effects of osteotomy placement and Chevron apex geometry within the surgical safe zone remain unclear. This study evaluated how oblique cut position and Chevron apex orientation affect construct stiffness and stress distribution using patient-specific finite element models. Weight-bearing CT-derived models of the distal tibia, talus, and calcaneus were generated for seven patients. Nine MDCO configurations were simulated per patient: three oblique cut positions (anterior, middle, posterior) and six Chevron configurations varying by apex angle (130°, 150°, 170°) and apex position (anterior, posterior), yielding 63 simulations. Models incorporated cortical–cancellous bone separation, frictional osteotomy contact, patient-specific body-weight loading, and simplified Achilles tendon and plantar fascia forces. Axial stiffness, screw top 5% average von Mises stress, and osteotomy top 5% average von Mises stress were compared using within-subject analyses. Oblique cut position did not significantly affect stiffness ( p = 0.149) or screw stress ( p = 0.349), but significantly affected osteotomy stress ( p < 0.001). Anterior oblique placement produced higher osteotomy stress (5.23 ± 1.25 MPa) than middle (4.18 ± 0.84 MPa, p = 0.005) and posterior placement (3.70 ± 0.98 MPa, p = 0.002). Chevron apex angle did not significantly affect any outcome. However, posterior Chevron apex placement produced higher osteotomy stress than anterior placement (4.79 ± 0.69 vs 4.07 ± 0.53 MPa, p = 0.011). These findings suggest that local osteotomy-surface stress is more sensitive to MDCO geometry than global stiffness or screw stress.